LO54: Emergency department prevalence of intracranial aneurysm on computed tomography angiography (EPIC-ACT). (May 2020) - Sheppard, B.; Beller, G.; O'Rielly, C.; Wong, Charles
Abstract : Introduction: Evidence is accumulating that a CT plus a CT angiogram (CTA) of the head and neck may be adequate to rule out subarachnoid haemorrhage (SAH) in patients with a thunderclap headache, thus potentially negating the need for lumbar puncture. One of the most widely cited objections to this strategy is the fear of detecting "incidental asymptomatic aneurysms, " lesions seen on angiography that are not in fact the cause of the patient's symptoms. Currently existing data on the background rate of aneurysms are based on cadaveric studies, invasive angiography, or MRI, and thus does not reflect the true rate of incidental aneurysms that would be detected using a CT plus CTA strategy. This study characterizes the rate of incidental aneurysms identified on CTA in an emergency department population. Methods: In this multicentre retrospective cohort study we analyzed the electronic medical records of all emergency department patients ≥ 18 years of age who underwent CTA of the head and neck over a two month period across four urban tertiary care emergency departments. Two independent reviewers evaluated the final radiology reports and extracted relevant data. The primary outcome of interest was the presence of incidental intracranial aneurysm, defined as a newly diagnosed aneurysm not associated with evidence of acute hemorrhage. Secondary outcomes included aneurysm location and size. Results: Of 739 charts meeting inclusion criteria, incidental intracranial aneurysms were detected in 21 cases or 2.85% (95% confidence interval, 1.77 - 4.32). An additional 20 aneurysms were identified but excluded from the analysis as they were previously known (n = 9) or were associated with evidence of acute hemorrhage (n = 11) and thus were not considered incidental. Of 21 patients with identified incidental aneurysms, 7 had multiple aneurysms. The most common aneurysm sites were internal carotid artery (n = 13), middle cerebral artery (n = 6) and anterior cerebral artery (n = 4). The average size of incidental aneurysm was 4.1 mm. Conclusion: The rate of incidental intracranial aneurysm among emergency department patients undergoing CTA of the head and neck is lower than many previously described estimates obtained through invasive angiography and MRI studies. To our knowledge, this is the first study on the prevalence of incidental intracranial aneurysms in an emergency department specific population and may therefore help guide clinicians when considering using a CT plus CTA rule out strategy for patients presenting with acute headache suspicious for SAH.